2012
DOI: 10.7439/ijpc.v2i3.679
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Study of Some Novel Benzimidazole Analogs as Potential Antiulcer Agents

Abstract: ABSTRACT:The present investigation is concerned with synthesis of new substituted benzimidazole derivatives 4a-4f with the objective of discovering novel and potent antiulcer agent. The structures of all the synthesized compounds were characterized by spectral and elemental analysis. The synthesized compounds were screened for their antiulcer activity at the doses of 10 and 20 mg / kg p. o. The compound 4d showed highest antiulcer activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Fur ther more, benzimidazole moiety is a crucial template in medicinal chemistry because of its wide variety of reported biological and pharmacological activities, some of which include anticancer 11 , antimicrobial 12 , antitumor 13 , antimalarial 14 ,anti-HIV 15 , anti-inflammatory 16 , antitubercular 17 , anthelmintic 18 , anticonvulsant 19 , antioxidant 20 , anti-ulcer 21 , anti-HBV 22 , among others. The pharmacological investigation showed that the antagonism of Ang II-induced pressure response by oral administration of a series of benzimidazole hybrid was obviously superior to that of clinical drug standard used.…”
Section: -9mentioning
confidence: 99%
“…Fur ther more, benzimidazole moiety is a crucial template in medicinal chemistry because of its wide variety of reported biological and pharmacological activities, some of which include anticancer 11 , antimicrobial 12 , antitumor 13 , antimalarial 14 ,anti-HIV 15 , anti-inflammatory 16 , antitubercular 17 , anthelmintic 18 , anticonvulsant 19 , antioxidant 20 , anti-ulcer 21 , anti-HBV 22 , among others. The pharmacological investigation showed that the antagonism of Ang II-induced pressure response by oral administration of a series of benzimidazole hybrid was obviously superior to that of clinical drug standard used.…”
Section: -9mentioning
confidence: 99%
“…The 4-methoxy phenyl piperazine substituted benzimidazole derivative (183) appeared to be the most effective agent (Patil et al, 2012). Chang et al (Chang et al, 2012) (Rajesh et al, 2017).…”
Section: Antiulcer Activitymentioning
confidence: 99%
“…Moreover, some benzimidazole-piperazine conjugated analogues were assessed for their in vivo antiulcer property. The 4-methoxy phenyl piperazine substituted benzimidazole derivative (183) appeared to be the most effective agent ( Patil et al, 2012 ). Chang et al ( Chang et al, 2012 ) developed a series of 3,4,5-trimethoxybenzylbenzimidazole derivatives among which compound 184 (2-fluorophenyl-5-methyl-1-(3,4,5-trimethoxybenzyl) benzimidazole) emerged as the most potent inhibitor of Helicobacter pylori growth and pathogenesis of host cells.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Imidazole is a five-membered aromatic heterocycle that exhibits a number of biological applications, such as antibacterial [18], anticancer [19], antiepileptic [20], antitubercular [21] activities, etc. Benzimidazoles are privileged structures related to their roles in medicinal chemistry, e.g., they play their role in antibacterial [22], antidiabetic [23], antiviral [24], antiulcer [25] activities, etc. Drugs containing quinazoline, imidazole, and benzimidazole are given in Figure 1.…”
Section: Introductionmentioning
confidence: 99%